Fodor's Pacific Northwest 2024 - Arenas, Shelley, 1958- (Fodor's Travel, a division of MH Sub I, LLC, dba Internet Brands, 2023)
"Whether you want to visit a stunning national park, go wine-tasting in Oregon's Willamette Valley, or experience the culture of Seattle, Portland, or Vancouver, the local Fodor's travel experts in the Pacific Northwest are here to help! Fodor's Pacific Northwest guidebook is packed with maps, carefully curated recommendations, and everything else you need to simplify your trip-planning process and make the most of your time"--